Study of the association between 3111T/C polymorphism of the CLOCK gene and the presence of overweight in schoolchildren - Nayara P. Giovaninni; Jeanne T. Fuly; Leonardo I. Moraes; Thais N. Coutinho; Ericka B. Trarbach; Alexander A. de L. Jorge; Everlayny F. Costalonga (Elsevier, 2014)
Objectives: To evaluate the association between 3111T/C polymorphism of the CLOCK gene and the presence of obesity and sleep duration in children aged 6‐13 years. In adults, this genetic variant has been associated with duration of sleep, ghrelin levels, weight, and eating habits. Although short sleep duration has been linked to obesity in children, no study has aimed to identify the possible molecular mechanisms of this association to date. Methods: Weight, height, and circumferences were transformed into Z‐scores for age and gender. Genotyping was performed using TaqMan methodology. A questionnaire regarding hours of sleep was provided to parents. The appropriate statistical tests were performed. Results: This study evaluated 370 children (45% males, 55% females, mean age 8.5 ± 1.5 years). The prevalence of overweight was 18%. The duration of sleep was, on average, 9.7 hours, and was inversely related to age (p < 0.001). Genotype distribution was: 4% CC, 31% CT, and 65% TT. There was a trend toward higher prevalence of overweight in children who slept less than nine hours (23%) when compared to those who slept more than ten hours (16%, p = 0.06). Genotype was not significantly correlated to any of the assessed outcomes. Conclusions: The CLOCK 3111T/C polymorphism was not significantly associated with overweight or sleep duration in children in this city. Resumo: Objetivos: Avaliar a relação entre o polimorfismo 3111 T/C do gene CLOCK (rs1801260) e a presença de obesidade, bem como a duração do sono, em crianças de 6 a 13 anos. Em adultos, essa variante genética foi associada à duração do sono, níveis de grelina, peso e padrão alimentar. Embora, em crianças, a curta duração do sono tenha sido relacionada à obesidade, até o momento nenhum estudo foi direcionado no sentido de identificar possíveis mecanismos moleculares dessa associação. Métodos: Peso, altura e circunferências foram transformados em escores‐Z para idade e sexo. A genotipagem foi realizada pela metodologia Taqman. Um questionário sobre horas de sono foi entregue aos pais. Testes estatísticos apropriados foram realizados. Resultados: Foram avaliadas 370 crianças (45% meninos, 55% meninas, idade média 8,5±1,5 anos). A prevalência de excesso de peso foi de 18%. A duração do sono foi, em média, 9,7 horas, sendo inversamente relacionada à idade (p < 0,001). A distribuição genotípica foi: 4% CC, 31% TC e 65% TT. Houve uma tendência de maior prevalência de excesso de peso em crianças que dormiam menos de 9 h (23%), quando comparadas às que dormiam mais de 10 h (16%, p = 0,06). O genótipo não se correlacionou significativamente a nenhum dos desfechos avaliados. Conclusões: O polimorfismo CLOCK 3111 T/C não está significativamente associado ao excesso de peso ou à duração do sono em crianças desta localidade. Keywords: Childhood obesity, Duration of sleep, CLOCK, Polymorphism, Palavras‐chave: Obesidade infantil, Duração do sono, CLOCK, Polimorfismo